Alternating current curing of conductive fly ash-slag geopolymer mortars: performance, characterization and optimization - Aygun, Beyza Fahriye; Uysal, Mucteba; Bilir, Turhan; Cosgun, Turgay; Dilbas, Hasan (SPRINGERNATURE, 2024)
This research seeks to pinpoint the most robust series by subjecting geopolymer mortars (GMs) to electrical curing (AC) at 20 V based on different NaOH concentrations and GBFS/FA ratios. To enhance the electrical conductivity of GMs displaying optimal mechanical properties, carbon fiber (CF), steel fiber (SF), waste wire erosion (WWE) (0.25%, 0.50%, and 0.75%), and carbon black (CB) (1%, 2%, and 3%) were introduced into the chosen series. A comprehensive assessment encompassing compressive strength, flexural strength, ultrasonic pulse velocities, direct tensile strength and splitting tensile strengths were conducted on mixtures undergoing 24 h of AC. The study's findings indicated a substantial improvement in mechanical properties through electrical curing compared to ambient curing conditions. Notably, a correlation of up to 99% was established between direct and splitting tensile properties. The investigation revealed that the highest compressive strength, reaching 72.41 MPa at 1 day strength, was achieved through the thermal curing method with electric curing, particularly in the 100GBFS series. On the other hand, the optimum bending strength, approximately 19 MPa, was observed in the SFA075WWE series. These results highlight the efficacy of the thermal curing method with electric curing in enhancing the compressive strength of the 100GBFS series and the flexural strength of the SFA075WWE series, underscoring the potential benefits of specific curing methods for different series within the study.
Keywords: Geopolymer mortars; Fibers; Mechanical properties; Electrical curing; Electrical heating; MCDM; CONCRETE; Engineering; Materials Science